2016
DOI: 10.2337/dc16-1353
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Canagliflozin, a Sodium Glucose Cotransporter 2 Inhibitor, on Glycemic End Points Assessed by Continuous Glucose Monitoring and Patient-Reported Outcomes Among People With Type 1 Diabetes

Abstract: Canagliflozin improved indices of glycemic variability and was associated with improvement in treatment satisfaction versus placebo over 18 weeks among participants with type 1 diabetes. Although these data from this study demonstrate the potential benefits of canagliflozin in people with type 1 diabetes, canagliflozin is not approved for the treatment of type 1 diabetes and should not currently be used in people with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 46 publications
6
66
0
2
Order By: Relevance
“…Today it is feasible to utilize CGM to compare treatment regimens with other interventions, other active agents, or placebo. This has been applied to rapid-acting 72,73 and long-acting 74 insulins, SGLT 2 inhibitors, 75 GLP-1 RAs, 72,76,77 and other classes 78 of medications. CGM is critical when we wish to compare GV for different forms of therapy, evaluate nocturnal patterns, frequency, severity, and duration of hypo-and hyperglycemia, and postprandial patterns.…”
Section: Impact Of Cgm On Clinical Trials Of New Therapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today it is feasible to utilize CGM to compare treatment regimens with other interventions, other active agents, or placebo. This has been applied to rapid-acting 72,73 and long-acting 74 insulins, SGLT 2 inhibitors, 75 GLP-1 RAs, 72,76,77 and other classes 78 of medications. CGM is critical when we wish to compare GV for different forms of therapy, evaluate nocturnal patterns, frequency, severity, and duration of hypo-and hyperglycemia, and postprandial patterns.…”
Section: Impact Of Cgm On Clinical Trials Of New Therapeutic Agentsmentioning
confidence: 99%
“…It would be helpful if CE and FDA would make an unambiguous declaration that they will accept CGM data as part of the formal evaluation of new forms of therapy. The improving accuracy, ease of use, duration of use, user acceptance, reduced costs of CGM systems, and the success of studies reported to date [72][73][74][75][76][77][78] should spur increasing use of CGM in clinical trials.…”
Section: Impact Of Cgm On Clinical Trials Of New Therapeutic Agentsmentioning
confidence: 99%
“…[5][6][7][8][9][10] Use of SGLT2 inhibitors was associated with improvements in average glucose control, reduced postprandial hyperglycemia and glycemic variability, reduced body weight, and reduced insulin dose requirements. [11][12][13] Dual SGLT1/2 inhibitor, sotagliflozin, has also demonstrated significant reductions in HbA1c, postprandial glucose, weight, and insulin doses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these drugs appears to be increasing in young people with T1D despite not being approved 1,[27][28][29][30] . This case illustrates the risk of using these promising drugs when long-term safety studies are lacking.…”
Section: Discussionmentioning
confidence: 99%